Severe Hyperkalemia and Bilateral Adrenal Metastasis - Nagler, Michael (Hindawi Publishing Corporation, 2009)
Adrenal metastases are a common finding in metastatic lung and breast cancer. Often there are no clinical symptoms suggesting them. In this paper, we present a case of a 66-year-old man with metastatic lung cancer suffering from severe hyperkaliemia due to hypoaldosteronism as a result of bilateral adrenal metastasis.